PENGARUH PENGEMASAN TERHADAP MUTU BUAH PISANG KEPOK (Musa paradisiaca.L) PADA PENGANGKUTAN DARI PULAU BIARO KE MANADO - Yuliana Lisawengeng; Frans Wenur; Ireine A. Longdong (Universitas Sam Ratulangi, 2019)
ABSTRACT The handling of Kepok bananas within inter-island transportation in Biaro, SITARO Regency is still traditionaly, therefore Kepok bananas suffer mechanical damage such as bruises, scratches, and broken wounds. Good handling steps are needed in the transportation process so that the product can arrive in the hands of consumers in good quality conditions. This study aims to determine a good packaging that is able to withstand pressure and friction during the transportation of Kepok banana fruit from Biaro to Manado. Research using the Experimental Method with Descriptive Analysis. The packaging consisting ofÂ plastic sacks, cardboard packaging and wooden box packaging. Kepok bananas are packaged according to available packaging and transported by ship from Biaro Harbor to the Ferry Port in Munte then by land transportation to Manado. The results showed that the highest mechanical damage during transportation was found in Kepok bananas packed with plastic sacks at 41.84%, followed by Kepok bananas packed with cardboard with a damage value of 36.56%. Meanwhile, the lowest level of mechanical damage was in bananas packed with wooden boxes at 32.59%. Keywords: Postharvest Handling, Transportation, Packaging